The Effect of Nitrogen Starvation on Biomass Yield and Biochemical Constituents of Rhodomonas sp. - Latsos, Christos; van Houcke, Jasper; Timmermans, Klaas R. (Frontiers in Marine Science, 2020)
The microalga Rhodomonas sp. is known as an excellent feed source for live feed organisms such as copepods. The main benefits of feeding Rhodomonas to live feed animals are attributed to the relative high polyunsaturated fatty acid (PUFA) level, the combination of containing both docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), and the ratio between these fatty acids (FA). It has been shown that microalgae are able to accumulate valuable metabolites, such as lipids, under adverse conditions. The easiest and most inexpensive method to induce stress to microalgae is through nitrogen (N) starvation. In this study, the effect of N-starvation on biomass concentration, cell volume, and cellular composition, such as fatty acid concentration and composition, and phycoerythrin (PE) concentration of Rhodomonas sp. during a period of eight days, was investigated. The research was divided into two stages. In the first (growth) stage, Rhodomonas sp. was cultivated in small 400 ml photobioreactors (Algaemist-S) under optimal conditions in turbidostat mode, which reached a biomass concentration of 1.5 gDW L-1 and dilution rate of 1.3 d-1. Samples were taken every 24 hours for cell density and volume and productivity measurements in order to ensure a healthy and stable culture. In the next stage (N-starvation), the biomass was washed and transferred in a reactor filled with N-depleted medium. During N-starvation, samples were taken for biomass concentration, cell volume, PE and FA composition. The results of this study demonstrate that the lipid content increased significantly from 9% (t=0 hours) to 30% (t=120 hours) of the dry weight. After 120 hours of N-starvation, the total FA content of Rhodomonas sp. remained stable for the remainder of the experiment (next 72 hours). The highest increase of the FA concentration was represented by C16:0, C:18:1, C18:2, and C18:3, with highest concentrations after 120 hours of starvation. The maximum EPA and DHA concentrations were observed after 48 hours of starvation, while the maximum DHA to EPA ratio was detected at the end of the starvation.